Wild, wild wolves - Milton, Joyce; Schwinger, Larry (New York : Random House, 1992)
Introduces the natural history of wolves, examining their social structure, hunting tactics, growth, and development, and explores myths and legends about them.
"Grades 1-3"--Cover.
Keywords: Wolves -- Juvenile literature; Wolves